Outcomes of Preterm Infants With Congenital Heart Defects After Early Surgery: Defining Risk Factors at Different Time Points During Hospitalization - Cheung, Po-Yin; Hajihosseini, Morteza; Dinu, Irina A.; Switzer, Heather; Joffe, Ari R.; Bond, Gwen Y.; Robertson, Charlene M. T. (Frontiers in Pediatrics, 2021)
Background Compared with those born at term gestation, infants with complex congenital heart defects (CCHD) who were delivered before 37 weeks gestational age and received neonatal open-heart surgery (OHS) have poorer neurodevelopmental outcomes in early childhood. We aimed to describe the growth, disability, functional, and neurodevelopmental outcomes in early childhood of preterm infants with CCHD after neonatal OHS. Prediction models were evaluated at various timepoints during hospitalization which could be useful in the management of these infants. Methods We studied all preterm infants with CCHD who received OHS within 6 weeks of corrected age between 1996 and 2016. The Western Canadian Complex Pediatric Therapies Follow-up Program completed multidisciplinary comprehensive neurodevelopmental assessments at 2-year corrected age at the referral-site follow-up clinics. We collected demographic and acute-care clinical data, standardized age-appropriate outcome measures including physical growth with calculated z-scores; disabilities including cerebral palsy, visual impairment, permanent hearing loss; adaptive function (Adaptive Behaviour Assessment System-II); and cognitive, language, and motor skills (Bayley Scales of Infant and Toddler Development-III). Multiple variable logistic or linear regressions determined predictors displayed as Odds Ratio (OR) or Effect Size (ES) with 95% confidence intervals. Results Of 115 preterm infants (34±2 weeks gestation, 2339±637g, 64% males) with CCHD and OHS, there were 11(10%) deaths before first discharge and 21(18%) deaths by 2-years. Seven (6%) neonates had cerebral injuries, 7 had necrotizing enterocolitis; none had retinopathy of prematurity. Among 94 survivors, 9% had cerebral palsy and 6% had permanent hearing loss, with worse outcomes in those with syndromic diagnoses. Significant predictors of mortality included birth weight z-score [OR 0.28(0.11,0.72), p=0.008], single-ventricle anatomy [OR 5.92(1.31,26.80), p=0.021], post-operative ventilation days [OR 1.06(1.02,1.09), p=0.007], and cardiopulmonary resuscitation [OR 11.58 (1.97,68.24), p=0.007]; for adverse functional outcome in those without syndromic diagnoses, birth weight 2000-2499g [ES -11.60(-18.67,-4.53), p=0.002], post-conceptual age [ES -0.11(-0.22,0.00), p=0.044], post-operative lowest pH [ES 6.75(1.25,12.25), p=0.017], and sepsis [ES -9.70(-17.74,-1.66), p=0.050]. Conclusion(s) Our findings suggest preterm neonates with CCHD and early OHS had significant mortality and morbidity at 2-years and were at risk for cerebral palsy and adverse neurodevelopment. This information may be important for management, parental counseling and the decision-making process.